The art of electronics - Horowitz, Paul, 1942-; Hill, Winfield (Cambridge [England] ; New York : Cambridge University Press, 1989)
This book is about: Foundations; Transistors; Field-effect transistors; Feedback and operational amplifiers; Active filters and oscillators; Voltage regulators and power circuits; ...
Keywords: Electronics; Electronic circuit design; Electronics; Electronic circuit design